2019
DOI: 10.3390/insects10010014
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Phytochemicals, Honey Bee Longevity and Pathogen Tolerance

Abstract: Continued loss of natural habitats with native prairies and wildflower patches is eliminating diverse sources of pollen, nectar and phytochemicals therein for foraging bees. The longstanding plant-pollinator mutualism reiterates the role of phytochemicals in sustaining plant-pollinator relationship and promoting honey bee health. We studied the effects of four phytochemicals—caffeine, gallic acid, kaempferol and p-coumaric acid, on survival and pathogen tolerance in the European honey bee, Apis mellifera (L.).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
66
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(70 citation statements)
references
References 57 publications
4
66
0
Order By: Relevance
“…and Aster scaber Thunberg, at non-toxic concentrations, proved to show anti-nosemosis effects [ 28 , 29 ]. In several studies, essential oils such as mint ( Mentha pepper L.), melissa ( Melissa officinalis L.), coriandrum ( Coriander sativum L.), thyme ( Satureja hortensis L.) oils, other phytochemicals such as caffeine, clove oil, gallic acid, kaempferol and p-coumaric acid, and even propolis expanded honeybee longevity and to some extent, reduced nosemosis levels [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. Such phytochemicals as clove oil, laurel extract and sulforaphane, moderately decreased Nosema -infection, but at the same time, strongly reduced honeybee lifespan [ 33 , 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…and Aster scaber Thunberg, at non-toxic concentrations, proved to show anti-nosemosis effects [ 28 , 29 ]. In several studies, essential oils such as mint ( Mentha pepper L.), melissa ( Melissa officinalis L.), coriandrum ( Coriander sativum L.), thyme ( Satureja hortensis L.) oils, other phytochemicals such as caffeine, clove oil, gallic acid, kaempferol and p-coumaric acid, and even propolis expanded honeybee longevity and to some extent, reduced nosemosis levels [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. Such phytochemicals as clove oil, laurel extract and sulforaphane, moderately decreased Nosema -infection, but at the same time, strongly reduced honeybee lifespan [ 33 , 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…The screening process also revealed that neither p -coumaric acid nor quercetin were capable of improving the survivorship of honey bees inoculated with IAPV ( Figure 1 D). Both of these phytochemicals possess multiple survivorship-boosting capabilities, including reducing N. ceranae spore load, upregulating detoxification genes, and increasing pesticide tolerance [ 25 , 26 , 27 , 29 ]. Furthermore, they both inhibit the replication and production of a large number of viruses, such as Canine Distemper Virus [ 30 ], human rhinovirus [ 31 ], herpes simplex virus [ 63 ], and Japanese encephalitis virus [ 64 ], although these tests have thus far been conducted only in mammalian systems.…”
Section: Discussionmentioning
confidence: 99%
“…Both, when ingested, upregulate genes that encode cytochrome P450 monooxygenase enzymes, which are responsible for the detoxification of xenobiotics [ 25 , 26 , 27 ]. PCA also upregulates antimicrobial peptide gene expression when fed to larval and adult bees [ 25 , 28 ] and improves honey bee survivorship when infected with Nosema ceranae microsporidian gut parasites [ 29 ]. Both PCA and quercetin have also been shown to possess antiviral qualities; however, these studies have primarily been conducted in human pathogen models (e.g., cell culture systems with model human viruses) [ 30 , 31 ] and not pollinators that normally collect and consume these phytochemicals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently caffeine is reported to be a potential antimicrobial that could reduce disease load in honeybees caused by Nosema bombi (Dissociodihaplophasida: Nosematidae) (Bernklau et al 2019) thereby offering an additional benefit to the pollinators that provide this most important service to plants. Although Richardson et al (2015a, b) reported no effect against another parasite, Crithidia bombi (Trypanosomatida).…”
Section: Caffeine Enhances Bee Memory and Learningmentioning
confidence: 99%